Analysis of the participation of a university hospital in a national program for breast reconstruction - Aleksandra Markovic; Salustiano Gomes de Pinho Pessoa (Revista Brasileira de Cirurgia Plástica)
Introduction: Despite advances in conservative surgeries, mastectomy is still a commonly performed procedure. However, many patients are unable to undergo immediate reconstruction. Such patients are integrated into a growing queue for restorative surgery. With the intention of reducing this demand, surgical Task Force programs were created. The objective of this study was to analyze the results of the second National Task Force of Breast Reconstruction (NTFBR), performed at the Plastic Surgery Service of Walter Cantídio University Hospital (SCPMRHUWC). Method: A prospective cohort study was conducted, in which 16 patients underwent breast reconstruction at SCPMRHUWC. The patients were followed up for 6 months, and their data were tabulated and analyzed. Results: All 16 female patients underwent breast reconstruction after mastectomy. The patients' ages ranged from 39 to 72 years. Among the early complications, seroma in the dorsal region (13%), partial necrosis of the mastectomy skin (6%), partial dehiscence of the operative wound (13%), and necrosis of the large dorsal flap (6%) were observed. None of the patients had late complications. The period of hospitalization ranged from 1 to 5 days. All patients who were in the SCPMR-HUWC queue for surgery were operated on. Conclusions: In this study, a high degree of satisfaction was verified by the operated patients, and good results were obtained with few functional complications. Thus, we conclude that the Task Force of breast reconstruction after mastectomy is a viable alternative in terms of public health.